Variation and Association of Cup Quality Attributes and Resistance to Coffee Berry Disease in Coffea Arabica L. Composite Cultivar, Ruiru 11 - Gichimu, Bernard M.; Gichuru, E. K.; Mamati, George E.; Nyende, A.B. (My University, 2013)
Majority of reported work on coffee breeding primarily concerns agronomic improvement that directly impinges on coffee quality. However, it is crucial that coffee breeding programmes for disease resistance also include coffee quality improvement since consumer awareness about the quality of different coffees has increased. The aim of this study was to determine the variation and associations of cup quality parameters and resistance against Coffee Berry Disease (CBD) in Coffea arabica L. cultivar Ruiru 11 hybrid sibs. The study also aimed at selecting specific Ruiru 11 sibs that combines good cup quality with high CBD resistance. Thirty four full-sib families representing this hybrid cultivar grown in three different agro climatic zones in Kenya were used for the study. Evaluation of CBD resistance was conducted through hypocotyl inoculation in a laboratory set-up. The study demonstrated existence of a high variation in cup quality and CBD resistance among Ruiru 11 sibs. A highly significant positive correlation was observed between all cup quality traits but there was either negative or no correlation between most cup quality traits and CBD resistance.
Keywords: Arabica Coffee; Ruiru 11 Sibs; Cup Quality; Coffee Berry Disease; Kenya